Preventing Alcohol Abuse among Early Adolescents through Family and Computer-Based Interventions: Four-Year Outcomes and Mediating Variables - Schinke, Steven (2006)
III-timed and excessive use of alcohol is associated with multiple and irreversible disabilities. The relationship between perinatal alcohol use and developmental disabilities, including fetal alcohol syndrome, is well documented. Empirical evidence also links alcohol use to a host of other developmental and physical problems among the offspring of drinkers and among drinkers themselves. Toward advancing the science of how to reduce alcohol abuse risks, this study developed and tested family and computer-based approaches for preventing alcohol use among a community sample of inner-city minority youth. Original findings from 4-year follow-up data obtained from over 90% of the study sample document continued positive program outcomes and shed light on cognitive problem solving, peer, and family mediators of alcohol use risk and protective factors among target youth.